Publication metrics: Types, utility, and caveats - Durga Prasanna Misra (Indian Journal of Rheumatology)
Publication metrics enable the assessment of the performance of citations or utilization of published work. Journal-level metrics depend on the database whose citations are analyzed. Publication metrics from the Web of Science include the widely-used journal impact factor (JIF) and other indices such as Journal Citation Impact, Eigenfactor, normalized Eigenfactor, and Article Influence Score. Metrics from Scopus include the CiteScore, Source Normalized Impact Factor, and SCImago Journal Rank. Author-level metrics such as total citations, h-index, i10-index, and g-index inevitably increase with time and can be inflated by self-citations. Article-level metrics such as total citations and online attention scores derived from Scopus (PlumX Metrics) or Altmetric indicate the extent of utilization and discussion in scientific circles of a particular article. Publication metrics are useful to provide a bird's eye view of how well an individual journal or article has been cited or used. They do not necessarily reflect article quality. As an example, some of the articles with the highest Altmetric Attention Scores are actually retracted publications that attained high scores due to the negative debate that they elicited. Journal-level metrics such as the JIF are fluid and prone to historical fluctuations from year to year, most recently observed by increases in the JIF of journals which published a lot of coronavirus disease 19-related content. Research assessment of individual scientists often misuses publication metrics such as the JIF, when they should instead rely on a critical appraisal of research articles by assessors.